The Right of Confrontation - Robert B. McKay (Washington University Law Quarterly, 1959)
It has long been clear that the first amendment admonition that "Congress shall make no law . . ." involves something less than a categorical negative; similarly, the test of whether particular prohibitions of the Bill of Rights are also limitations upon the states has all the vagueness of the due process clause of the fourteenth amendment and none of the specificity of the particularized guarantees of the Bill of Rights. Thus, "the concept of ordered liberty" is the perfect foil for the relativist's" on the one hand" and on the other hand" argument. The purpose of this Article, however, is not to criticize this doctrine. Rather these examples are intended as illustrations of the inherent difficulties involved. One can scarcely expect that particular solutions to the vital problems of a dynamic constitution will be lastingly satisfactory. It is the intention in this study to explore a single area of constitutional dogma where the writer believes that the balancing of opposing interests, without proper regard for their qualitative differences, has led the federal courts into serious error. The problem may be simply stated: To what extent, and in what circumstances, does the national security interest justify the submerging of the otherwise fully assured right of a person to be confronted by his accusers?
Keywords: Civil rights; Loyalty oaths